ANALISIS PENENTUAN HARGA POKOK PRODUKSI KOPI PADA UMKM THE COFFEE LEGEND DI DESA SIPATUHU KECAMATAN BANDING AGUNG KABUPATEN OKU SELATAN - Anis Feblin; Feby Ariska (KOLEGIAL, 2019)
The purpose of this study was to determine the determination of the cost of coffee production at UMKM The Coffee Legend in Sipatuhu Village, Banding Agung Sub-District, South OKU Regency. The method used is descriptive quantitative by using the full costing method. The results of the analysis concluded that from the calculation of the cost of production using the full costing method can be known from 2017-2018 fluctuations occur, where the lowest cost of production occurs in July 2017 amounting to Rp2,396,100 and the highest cost of production occurred in October 2018 Rp27,096,400. The rise and fall of cost of production is caused by the most contributing, namely raw material costs because the price of raw materials is determined by the high and low exchange rate of the rupiah and the price of coffee purchased from coffee farmers.